Barriers and facilitators for interventions to improve ART adherence in Sub-Saharan African countries: A systematic review and meta-analysis - Buh, Amos; Deonandan, Raywat; Gomes, James; Krentel, Alison; Oladimeji, Olanrewaju; Yaya, Sanni (Université d'Ottawa | University of Ottawa, 2023)
The HIV/AIDS pandemic remains a significant public health issue, with sub-Saharan Africa (SSA) at its epicentre. Although antiretroviral therapy (ART) has been introduced to decrease new infections and deaths, SSA reports the highest incidence of HIV/AIDS, constituting two-thirds of the global new infections. This review aimed to elucidate the predominant barriers and facilitators influencing ART adherence and to identify effective strategies to enhance ART adherence across SSA.
Keywords: Adult; Adolescent; Child; Humans; Female; Pregnancy; Prospective Studies; Cross-Sectional Studies; Retrospective Studies; Medication Adherence; Acquired Immunodeficiency Syndrome; HIV Infections